If you're reading this, it's too late - Bosch, Pseudonymous (Secret series, 2014)
Cass and Max-Ernest discover the Museum of Magic, unscramble more coded messages, and solve new mysteries in their attempt to thwart the Terces Society's ambitions of discovering immortality.